A comparative evaluation on the cleaning and shaping ability of three nickel titanium rotary instruments using computerized tomography - An ex vivo study - Narayan, Gopal S. (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: Successful root canal treatment depends primarily on the removal of micro-organisms through chemo-mechanical instrumentation of the root canal system. This encompasses shaping by mechanical removal of the dentine and cleaning by chemical disinfection of microorganisms and dissolution of organic tissues from the root canal. While root canal shaping can be predictably and efficiently attained with advanced instrumentation technology, effective cleaning of the entire root canal system remains a challenge. Rotary nickel titanium instruments are known for their efficient preparation of root canal. This is mainly because of the super elasticity of the nickel titanium alloy which gives an increased flexibility and allows the instrument to efficiently follow the original path of root canal. The purpose of this study is to compare the cleaning efficiency and shaping ability of M two, K3, Race ni-ti rotary instruments during the preparation of curved canals in extracted molars. MATERIALS AND METHODS: Thirty teeth with 18 mm as their working length were selected and divided into three groups of 10 teeth each Angle of curvature, Radius of curvature, was determined using computerized tomography. A Pre and Post-operative measurement of canal width and volume was recorded and compared using CT. The teeth was then sectioned into two halves and subjected to scanning electron microscope. Images were taken at the level of apical third, middle third and coronal third for debris and smear layer. Scoring was done separately for both debris and smear layer. RESULTS: Results were tabulated and statistically analyzed to evaluate the shaping ability and cleaning efficiency. Instruments were examined for any deformation or fracture during canal preparation. CONCLUSION: M two showed greater enlargements in all the three levels, when compared its width and volume, with other two instruments. K3 was better than Race when compared among them. In the scanning electron microscope study for debris and smear layer M Two performed better followed by K3 and Race.